Pengaruh Dimensi Kualitas Pelayanan Terhadap Keputusan Pembelian pada Moris Bakery and Cake di Kota Langsa - Nurhafni Sabila; Erni Junaida; Dewi Rosa Indah (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2022)
AbstrakThis research was conducted with the aim of knowing the effect of service quality on purchasing decisions of Moris Bakery and Cake in Langsa City. The sampling technique used non-probability sampling technique with a sample size of 97 respondents. Methods of data collection using a questionnaire. The data analysis method used in this research is multiple linear regression test, t test, F test and coefficient of determination test. The results of this study show Y= -0.104 + 0.615X1 – 0.240X2 – 0.050X3 + 0, 247X4 + 0.430X5. The results of the t test stated that the tangible, assurance and empathy variables had a significant effect on purchasing decisions, and the reliability and responsiveness variables had no significant effect on the purchasing decisions of Moris Bakery and Cake in Langsa City. The results of the F test indicate that the variables tangible, reliability, responsiveness, assurance and empathy have a significant effect on purchasing decisions for Moris Bakery and Cake in Langsa City. The results of the coefficient of determination test (Adjusted R2) obtained a value of 0.749 or 74.9% tangible, reliability, responsiveness, assurance and empathy variables can explain the purchasing decision variables.Keywords: Service Quality, Purchase Decision